If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n = 4 + (n + 1)(-5) Reorder the terms: n = 4 + (1 + n)(-5) Reorder the terms for easier multiplication: n = 4 + -5(1 + n) n = 4 + (1 * -5 + n * -5) n = 4 + (-5 + -5n) Combine like terms: 4 + -5 = -1 n = -1 + -5n Solving n = -1 + -5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '5n' to each side of the equation. n + 5n = -1 + -5n + 5n Combine like terms: n + 5n = 6n 6n = -1 + -5n + 5n Combine like terms: -5n + 5n = 0 6n = -1 + 0 6n = -1 Divide each side by '6'. n = -0.1666666667 Simplifying n = -0.1666666667
| 2s=2s+6 | | 4(2x+7)=-30+26 | | 6x+19=63 | | -300=5(8a+4) | | -35x+42=-29x-6 | | 0=4x^2+12x+13 | | -8+4x=2x+18 | | -2(2x-9)-7x=30 | | 2(20y-20)=-5(20-12y) | | -5(x-4)-25=-5 | | -4x-4=-2x+12 | | 3p-15+3p=-27 | | 7X+10y=655 | | 900x+45= | | 8x-18=6x+2 | | 9=12t | | 110+t^2=190+2t | | -6+2x=8+3x | | -7(5n-16)=-7n | | t+75=4t | | b+9=4b | | -11+5x=4+6x | | 2(4x-3)-8=4(4-2x) | | s+81=2s | | -20h=-7(4h+20)-12 | | 90-2x=-5+3x | | x-40=-5x+50 | | -2.25(x-1.5)(x-6)=0 | | b+28=5b | | c+13=2c | | -x+0.25y-s=-1.75 | | -3x-14=-6x+25 |